Increase The Community By Cultivating An Entrepreneurial Spirit Through Nusantara Culinary "Ayam Geprek" in Rainbow Village Perlis, Malaysia - Justita Dura; Nur Lailatul Aqromi; Siti Nurul Afiyah; Wa Ode Irma Sari; Mulyaningtyas Mulyaningtyas; Mariana Puspa Dewi; Rifki Hanif; Hironimus Hari Kurniawan; Setyorini Setyorini; Adriani Kalalembang; Layli Dwi Rohmatunnisa; Puji Subekti (Jurnal Pengabdian Masyarakat, 2023)
Purpose: The purpose of this community service activity is to connect Indonesian local culture, especially through Ayam Geprek dishes, with international tourists visiting Rainbow Village Perlis, Malaysia. Method: This community service was carried out in Rainbow Village, Perlis, Malaysia. Its activities include a series of carefully planned stages. Preparation begins with an internal coordination meeting to draw up a detailed plan and divide tasks. Next, the team had a meeting with the local community and presented the concept of the project. Ayam Geprek cooking demonstration was conducted on the hall premises. Practical Applications: The results of the Ayam Geprek cooking demonstration activity showed a very positive response from international tourists in Malaysia. They rated this dish spicy but very tasty and impressive. This indicates the great potential of Ayam Geprek as a culinary attraction for tourists. The active involvement of the community in this activity also plays an important role in facilitating the introduction of Javanese cultural elements through Ayam Geprek dishes. Conclusion: Ayam Geprek cooking demonstration activities have been successful in achieving its goals. The positive response from international tourists shows the great potential of Ayam Geprek as a culinary attraction. It is hoped that this project will strengthen the relationship between Indonesia and Malaysia, particularly in the cultural and culinary context, as well as enrich the experience of international tourists in Malaysia.